تطوير معجم الكتاب بإندونيسي - Muhammad Amin (Abjadia, 2016)
في عصرنا الحاضر، يحتاج طلاب المدرسة معجم الكتاب. هذا المعجم لكتاب المدرسة في الفصل. كان أكثر الطلاب في المدارس الثانوية الإسلامية يواجهون الصعوبة في استخدام المعجم العادية مثل معجم المنور ومعجم محمود يونس. هم يحتاجون إلى المعجم المساعد، خاصة معجم الذي يصاحب كتاب التعليم المدروس في مدارسهم. هذا البحث يستخدام طريقة البحث والتطوير حيث يطور الباحث المعجم المساعد بخطوات معينة ليسهل الطلاب في بحثهم عن معاني المفردات الموجودة في كتاب التعليم. نتيجة البحث يشير على أن هذا المعجم المساعد (معجم الكاب) لديه فعالية استخدام العالي.In this modern era, the students need book dictionary. This dictionary is dictionary for text book in the class. There are many students in Islamic Senior High School face difficult when using general dictionary like Al-Munawwir dictionary and Mahmud Yunus dictionary. They need auxiliary dictionary, especially dictionary for learning book that they studied in their school. This research uses research and development method that the researcher develop auxiliary dictionary with certainly steps to facilitate students when they are looking for the meaning of vocabularies in the text book. Research result is that auxiliary dictionary has high effectiveness.